(untitled) (Archive of Conferences, 2022)
In recent years, at a time when the climate is warming, temperatures are rising sharply, desertification of arid areas is observed, the cultivation of pea crops on irrigated lands is bearing fruit. Water is needed for the seeds to germinate, and how much or how little water they absorb is very important.